The Development of Islamic Dentist Competence In Destistry Education - Musri Amurwaningsih; Titi Savitri Prihatiningsih; Ika Dewi Ana (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2017)
Background: The subject of dental health care has been receiving a lot of attention from Moslems in Indonesia, especially its accordance with Al-Qur’an and Sunnah. It has encouraged numerous researches which corelate dental health care through Islamic perspective, and ignored the perspective of dentistry. Consequently, this research is aimed to develop, formulate and validate the competence of moslem dentists.Method: Experts’ agreement was develop using Delphi method. The result then was developed into an instrument with 2 criteria was used to determine content validity index (CVI) and content validity ratio (CVR). The result was developed into a 5-point Likert scale instrument which would be used to determine internal consistency (Cronbach’s alpha) and corrected item–total correlation with Pearson’s correlation.Results: The qualitative method generated 4 domains. Domain shiddiq comprised 2 components, domain amanah 2 components, domain tabligh 2 components and domain fathonah 4 components with the value of agreement of each domain was approximately between 67% - 100%. The CVR value of the components of competence was between 0,69 – 1, while the CVI value was 0,877. The reliability test scored 0,923.Conclusion: The Competence Standards of Islamic Dentistry can be used as guidance for designing Islamic dental curriculum. Further research should be conducted to design assessment.